Analysis of Rice Buying and Selling with a Wholesale System to Increase Farmers' Income: An Islamic Business Ethics Perspective - Danang Suprayogi; Ahmad Muslimin; Agus Setiawan; Finny Ligery (CV. Bimbingan Belajar Assyfa, 2025)
The practice of buying and selling agricultural products with a wholesale system (al-jizaf) is widely found in various regions, including Way Panji District, South Lampung. This system is considered practical but raises questions regarding justice, transparency, and its impact on farmers' income. This study aims to analyze the practice of wholesale rice buying and selling, its impact on farmers' income, and its conformity with Islamic business ethics. The method used is qualitative with a case study approach. Data were collected through observation, in-depth interviews with three farmers and two contractors, and documentation. Data analysis used the Miles and Huberman model. The results show that the wholesale buying and selling practice is carried out through land surveys, sampling, price negotiations, down payment, and payment before harvest. This system does not significantly increase farmers' income (the difference is Rp200,000–500,000 lower than self-harvesting), but it is considered effective because farmers do not incur harvest operational costs. From the perspective of Islamic business ethics, this practice has fulfilled the principles of monotheism, justice, freedom of transaction, responsibility, and benevolence. Agreements are made through deliberation without coercion. Although there is an element of gharar (uncertainty), this is a minor gharar that is forgiven due to necessity and the buyer's expertise. This study recommends price transparency and providing farmers with the option of self-harvesting.